The Influence of Internal Control Systems and Accounting Information Systems on the Quality of Financial Statements of KSP Sena Group East Java - Shalshabilla, Imelia; Dwi Ermayanti Susilo (Cita Konsultindo Research Center, 2025)
This study aims to determine the effect of internal control systems and accounting information systems on the quality of financial statements of the Sena Group Savings and Loan Cooperative in East Java. This study holds an important position in the literature as it fills the gap in research regarding the relationship between the two variables, particularly in the cooperative sector, which often lacks the provision of modern information technology compared to other sectors. The method used is quantitative, with a population of 95 employees involved in financial report management. The sampling technique used is saturated sampling. Data was collected through questionnaires and analyzed using SPSS 25 software. The results of this study show that the internal control system has a positive but insignificant effect on the quality of financial statements, with a significance value of 0.489 > 0.05. Meanwhile, the accounting information system has a significant positive effect on the quality of financial statements, with a significance value of 0.000 < 0.05.